Comparing pediatric airway variability to standard laryngoscope sizes for 3D printing patient specific blades. (Transactions on Additive Manufacturing Meets Medicine, 2020)
Commercially available pediatric laryngoscope blades have limited variability in shape and sizes. Difficult airway intubations may require physicians to improvise in their selection of a patient’s blade size and could potentially lead to physical trauma and complications. With advancements in three-dimensional (3D) imaging, modeling, and printing, we are introducing a method for the design and fabrication of patient specific pediatric laryngoscopes at the point of care and comparing our methods to current industry standards.
Keywords: airway intubation; laryngoscope